Whitefly (Bemisia tabaci) Management Program for Ornamental Plants: ENY989/IN1171, 8/2021 - Kumar, Vivek; Ahmed, Muhammad Z.; Palmer, Cristi; McKenzie, Cindy L.; Osborne, Lance S. (EDIS, 2021)
Bemisia tabaci (Gennadius), commonly known as silverleaf whitefly, is a polyphagous pest and listed as one of the world’s 100 worst invasive species. It is known to feed on more than 1000 plant species and vector over 120 plant-damaging viruses. This publication provides a management program for nursery and ornamental plant growers to aid in their efforts to minimize selection for insecticide resistance irrespective of whitefly biotype while helping to achieve top-quality plant materials.